Presentation of the Dossier Crossings Italian-Luso-Afro-Brazilians: for na urgent ethical restoration of Humanism (languages and literatures today) - Canedo, Rogério Max (2024)
Presentation of the Dossier Italian-Portuguese-Afro-Brazilian Crossings: for an urgent ethical restitution of Humanism (languages ​​and literatures today), made by the organizers Rogério Max Canedo, Edvaldo A. Bergamo and Vera Lúcia de Oliveira.